Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Inquiri Terbimbing Pada Kelas VIII MTs Darussalam Beremi - Fitri, Ririn Arliana; Bahtiar; Sumartini, Sri (CAHAYA: Journal of Research on Science Education, 2023)
This study aims to improve student learning outcomes through the guided inqiry model in class VIII MTs Darussalam Beremi and identify student learning motivation. This research is a classroom research that uses steps, namely planning, implementation, evaluation and reflection. Data were collected using learning outcomes test instruments, motivation questionnaires. The results of this study are in cycle I obtained an average score of 60 so that it can be said that the learning outcomes of students were below the KKM, while in cycle II obtained an average score of 85 so it can be concluded that using the IT learning model can increase student motivation and learning outcomes.